Red army in Iran: Unknown «occupation» - B.Orishev, Aleksandr (2020)
The article is devoted to an actual topic, practically not covered in the historical literature and devoted to the stay of the Red Army in Iran during the Second World War. A legal assessment was given of the events of August 1941 - the entry of Soviet troops into Iran. The author proves that the actions of the government of the USSR from the point of view of international law cannot be characterized as «occupation». The article gives a detailed analysis of the Iranian claims regarding the stay of the Red Army units in Iran. Claims of both a material nature and with respect to the behavior of the Red Army are covered. It was proved that the overwhelming majority of claims were unfounded, and in those rare cases when the complaints of the Iranian side were based, the Soviet military authorities conducted thorough investigations, punishing the perpetrators. The article highlights the activities of the Red Army to ensure security of supplies under lend-lease, to combat banditry and terrorism on the Trans-Iranian railway, which transported military cargo to the USSR. The question of the relationship of soldiers and officers of the Red Army with the allies on the Anti-Hitler Coalition is being raised. The conclusion is drawn that the relations of the Red Army men with the Americans were more or less friendly. Soviet-British relations were tense. Also, the article raises issues related to the daily life of the Red Army in Iran - the problems they encountered in everyday life. The main scientific result obtained by the author is that the article substantiates the need for the Red Army to stay in Iran, stresses the importance of their contribution to the victory over Nazi Germany.